2015
DOI: 10.7567/jjap.54.106101
|View full text |Cite
|
Sign up to set email alerts
|

Laser absorption spectroscopy diagnostics of helium metastable atoms generated in dielectric barrier discharge cryoplasmas

Abstract: Cryoplasmas, which are plasmas whose gas temperatures are below room temperature (RT), have shown dynamic changes in their physical and chemical characteristics when the gas temperature in the plasmas (T gp ) was decreased from RT. In this study, we measured the temporal behavior of helium metastable (He m ) atoms generated in a parallel-plate dielectric barrier discharge at ambient gas temperatures (T ga ) of 300, 100, and 14 K and with a gas density similar to atmospheric conditions by laser absorption spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Stable, high-density plasmas can be generated at both low and high pressures and temperatures. [28][29][30][31] As an example, Ito et al reported that a micrometer-scale plasma discharge was successfully generated in supercritical CO 2 . 32) Thereafter, Meneoka et al demonstrated a dielectric barrier discharge between carbon nanotube electrodes in high-density N 2 .…”
Section: Other Polymorphs Of Nitrogenmentioning
confidence: 99%
“…Stable, high-density plasmas can be generated at both low and high pressures and temperatures. [28][29][30][31] As an example, Ito et al reported that a micrometer-scale plasma discharge was successfully generated in supercritical CO 2 . 32) Thereafter, Meneoka et al demonstrated a dielectric barrier discharge between carbon nanotube electrodes in high-density N 2 .…”
Section: Other Polymorphs Of Nitrogenmentioning
confidence: 99%
“…One exception only for cryogenic plasmas was reported in the literature for the He 2 excimer solvated in the liquid helium [11]: the lowest allowed rotational quantum state of the d 3 Σ u + state was exclusively populated. The presence of impurities in helium gas changes the emission spectra observed in different plasmas initiated by radiofrequency (RF), dielectric barrier discharge (DBD), corona, direct current (DC) discharges or by highly energetic particles [12,13,14,15,16,17,18,19,20]. Lowering the temperature of the helium gas usually causes decreasing of the impurity emission intensities accompanied by increasing of the emission intensity from the helium atoms and molecules [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of impurities in helium gas changes the emission spectra observed in different plasmas initiated by radiofrequency (RF), dielectric barrier discharge (DBD), corona, direct current (DC) discharges or by highly energetic particles [12,13,14,15,16,17,18,19,20]. Lowering the temperature of the helium gas usually causes decreasing of the impurity emission intensities accompanied by increasing of the emission intensity from the helium atoms and molecules [14,15]. Nevertheless, fast cooling (for T ≈ 100 K within time ~ 0.1 ms) of the helium plasma jet allows observation of intense emission from impurity species at temperatures ~ 10 K [12,16,18,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…18,22) Laser absorption spectroscopy has been used as a standard technique for the measurement of metastable 2 3 S atoms. [23][24][25][26][27] Millard et al evaluated the metastable atom density in a plasma generated by a stationary glow discharge. 23) The electrodes in their device had a parallel-plate configuration, with electrodes of 38 mm diameter spaced 18 mm apart.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we performed laser absorption spectroscopy measurements for the helium 2 3 S 1 -2 3 P 0,1,2 transitions [23][24][25][26][27] in a micro-hollow-cathode helium plasma to investigate the behavior of the metastable 2 3 S 1 atoms. The experimental technique adopted in this study is based on a previous study 28) of the 2 1 P-3 1 D transition, wherein two-dimensional spatial distributions of the electric fields, 2 1 P atomic density, gas temperature, and electron density were evaluated at a gas pressure of 10 kPa.…”
Section: Introductionmentioning
confidence: 99%